2023
DOI: 10.1186/s12245-023-00575-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral adrenal infarction and insufficiency associated with antiphospholipid syndrome and surgery: a case report

Yoshihito Iijima,
Masahito Ishikawa,
Nozomu Motono
et al.

Abstract: Background Antiphospholipid syndrome causes systemic arterial and venous thromboses due to the presence of antiphospholipid antibodies. Adrenal insufficiency is a rare complication of antiphospholipid syndrome that may result in fatal outcomes if left untreated. Therefore, we report adrenal insufficiency as a rare complication of bilateral adrenal infarction associated with antiphospholipid syndrome and trauma surgery. Case presentation A 64-year-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In addition, the lesion was also high-intensity on diffusion-weighted image due to restricted diffusion water molecules. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the lesion was also high-intensity on diffusion-weighted image due to restricted diffusion water molecules. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…On contrast CT/magnetic resonance imaging, the non-hemorrhagic AI had obviously poor or no enhancement. [ 6 ] Moschetta et al had found the “capsular sign,” with 100% specificity, in diagnosis of acute adrenal ischemia. [ 18 ] And the “capsular sign” is likely resulting from the residual blood supply of the adrenal capsular veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenously produced GCs provide basal anti-inflammatory effects, with an escalated secretion in response to inflammatory challenges [ 131 ]. Hence, animals and humans with adrenal insufficiency demonstrate amplified responses to minor injuries post-adrenalectomy [ 132 , 133 ]. This observation has prompted speculation regarding the potential role of insufficient GC secretion in response to trauma or infection in the pathogenesis of select chronic inflammatory disorders [ 134 , 135 ].…”
Section: Mechanistic Pathways Of Gc Action In Tumor Cellsmentioning
confidence: 99%